2010
DOI: 10.1038/ajg.2009.633
|View full text |Cite|
|
Sign up to set email alerts
|

Longitudinal Profiles of 15 Serum Bile Acids in Patients With Intrahepatic Cholestasis of Pregnancy

Abstract: The bile acid profiles and effects of treatment by UDCA implicate a role for taurine-conjugated bile acids in the syndrome of intrahepatic cholestasis of pregnancy. [corrected] With regard to individual bile acid profiles, pruritus gravidarum is a disorder quite distinct from intrahepatic cholestasis of pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
56
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 30 publications
6
56
0
4
Order By: Relevance
“…Real-time quantitative polymerase chain reaction (qRT-PCR) was used to measure liver expressions of bile acid metabolism enzymes, transporters, and nuclear receptors. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 7 7-dehydrocholic acid (7-DHCA), isodeoxycholic acid (isoDCA), apocholic acid (apoCA), 6-ketolithocholic acid (6-KLCA), 7-ketolithocholic acid (7-KLCA), 12 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 9 µL water (with 0.1% formic acid). After centrifugation, 5 µL supernatant was injected for measurement.…”
mentioning
confidence: 99%
“…Real-time quantitative polymerase chain reaction (qRT-PCR) was used to measure liver expressions of bile acid metabolism enzymes, transporters, and nuclear receptors. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 7 7-dehydrocholic acid (7-DHCA), isodeoxycholic acid (isoDCA), apocholic acid (apoCA), 6-ketolithocholic acid (6-KLCA), 7-ketolithocholic acid (7-KLCA), 12 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 9 µL water (with 0.1% formic acid). After centrifugation, 5 µL supernatant was injected for measurement.…”
mentioning
confidence: 99%
“…The present study (1) identified three sulfated progesterone metabolites, 5a-pregnan-3a,-20a-diol-3,20-disulfate, 5b-pregnan-3a-20a-diol-3-sulfate, and 5b-pregnan-3a-20a-diol-3,20-disulfate, that were present in ICP patients in serum samples obtained even at [9][10][11][12][13][14][15] Abbreviations: ICP, intrahepatic cholestasis of pregnancy; PG, pruritus gravidarum.…”
mentioning
confidence: 99%
“…Patients with these characteristics have been identified in several studies, being usually labeled as having pruritus gravidarum (PG), an enigmatic entity that does not carry the fetal risks of a genuine ICP. (5,(9)(10)(11) Table 1 summarizes clinical and biochemical data previously reported in patients with ICP and in normal pregnancies, (7) comparing them with a concurrent unreported cohort of patients with PG in whom pruritus appeared at the same gestational age but was slightly less severe than in patients with ICP. In three of these patients with PG, pruritus diminished spontaneously 1 week prior to delivery; and in another patient, pruritus disappeared in the final week of pregnancy, a phenomenon that was not observed in patients with a genuine ICP.…”
mentioning
confidence: 99%
“…Tribe et al (1) in their study published in this issue of the Journal evaluated prospectively the serum bile acid composition during 16 weeks of gestation and 4 weeks postpartum in a cohort of women with ICP ( n = 63), pruritus gravidarum ( n = 43), and normal pregnancy ( n = 26). Samples were analyzed using an HPLC-MS protocol with an electrospray interface (ESI-MS) allowing simultaneous measurement of the fi ve bile acids (CA, CDCA, LCA, deoxycholic acid, UDCA) and their taurine and glycine conjugates.…”
mentioning
confidence: 99%
“…(1) reported the results regarding longitudinal profi les of 15 serum bile acids in women with intrahepatic cholestasis of pregnancy (ICP) using a novel method of measurement. Th e bile acid values were compared with those of women with pruritus gravidarum and normal pregnancy.…”
mentioning
confidence: 99%